Feasibility analysis of single wire earth return system for potential application in rural electrification in Nigeria - Sani Sabo Mohammed; Nura Musa Tahir; Usman Bature Isyaku; Ahmad Bala Alhassan; Abdulrazak Sabo (International Journal of Advances in Applied Sciences, 2022)
Traditionally, three-phase networks are used to transmit electric power to consumers. However, due to its high initial cost, many isolated rural communities are yet to have access to electricity. Thus, the single wire earth return (SWER) architecture, which uses the earth as the return path, attracts significant cost savings. In this paper, the potential application of the SWER system for rural electrification in Nigeria was presented. The cost-effectiveness of the SWER system which is about 70% less than the three-phase configuration, is due to the need for fewer cables, pole-top fittings, switching, and protection devices. Initially, the dynamic modeling of the equivalent SWER system was derived for the MATLAB simulation analysis. The pertinent parameters of the realized system, namely, micro-former leakage reactance, the resistive and inductive value of the single-phase network, were determined and employed for the SIMULINK and the repetitive power flow analyses. The results obtained from the power flow analysis and the simulation models for different loading conditions were found to agree with an error margin of +5%. This demonstrates that the proposed prototype can be adopted to reduce the prevalent energy poverty and thereby improved the quality of life of rural dwellers in Nigeria.